1970
DOI: 10.13057/nusbiosci/n080108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biochar, cocopeat and sawdust compost on the growth of two dipterocarps seedlings

Abstract: Abstract. Marjenah, Kiswanto, Purwanti S, Sofyan FPM. 2016. The effect of biochar, cocopeat and saw dust compost on the growth of two dipterocarps seedlings. Nusantara Bioscience 8: 39-44. Good growing media contains enough nutrients, light textured, and have the capacity to hold water to create conditions that can support plant growth. The growing media used for propagation has several requirements, that is firm and dense to enhance the growth of stems, has the capability to hold water, guarantee the plant li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 3 publications
1
12
1
2
Order By: Relevance
“…However, all treatments gave high survival rate, more than 90%, including that of 100% biochar treatment. Biochar application on growth media in nursery also gave high survival for Dipterocarps seedlings (Marjenah et al 2016;Syahrinudin et al 2018). These demonstrate that the use of biochar as main media for raising seedlings in nursery is of interest for the replacement of the conventional media as the availability of these conventional media (topsoils) becoming scarce lately and the use of these conventional media subject to ecological degradation of its originremoving fertile topsoil from the system may lead to nutrient cycle disruption and nutrient shortage of the system.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, all treatments gave high survival rate, more than 90%, including that of 100% biochar treatment. Biochar application on growth media in nursery also gave high survival for Dipterocarps seedlings (Marjenah et al 2016;Syahrinudin et al 2018). These demonstrate that the use of biochar as main media for raising seedlings in nursery is of interest for the replacement of the conventional media as the availability of these conventional media (topsoils) becoming scarce lately and the use of these conventional media subject to ecological degradation of its originremoving fertile topsoil from the system may lead to nutrient cycle disruption and nutrient shortage of the system.…”
Section: Resultsmentioning
confidence: 84%
“…Nutrient enriched biochar promoted higher survival rate at all rates of biochar treatment (Table 2). These results suggest that the application of biochar soil amendment coupled with other materials such as fertilizer, sludge and composted organic wastes would further enhance the favorable conditions of plant growth media (Alburquerque et al 2013;Schimmelpfennig et al 2014;Marjenah et al 2016). The addition of these materials into biochar application may further improve nutrient availability, i.e.…”
Section: Resultsmentioning
confidence: 92%
“…However, all treatments gave a high survival rate, more than 90%, including 100% biochar treatment. Biochar application on growth media in the nursery also showed high survival for Dipterocarps seedling [13,58]. This demonstrated that biochar's use as the primary media for raising seedlings in the nursery is of interest.…”
Section: Resultsmentioning
confidence: 86%
“…Begitu juga pada usahatani jamur tiram ada beberapa kendala yang dialami oleh para petani jamur tiram. Kendala yang dialami para petani jamur yaitu kendala dalam bahan baku media tanam, kendala pada tingkat keberhasilan pembuatan baglog atau media tanam, kendala pada proses sterilisasi, lambatnya perkembangan miselium dan lain-lain (Sunandar et al, 2018) (Fatmawati, 2017;Hasriani et al, 2013a;Prasetyawan, 2009;Rambey et al, 2018) Penelitian media limbah serbuk sabut kelapa dan limbah serbuk gergaji secara teknis cukup banyak dilakukan seperti untuk pertumbuhan padi (Antoro & Nelvia, 2018;Yulia et al, 2018), bibit kakao (Hasriani et al, 2013b;Saputra et al, 2019), kelapa sawit (Andri et al, 2017, pembibitan meranti (Marjenah, 2016), kentang (Putra et al, 2019), hidroponik (Hasriani et al, 2013a;James et al, 2010), tanaman hias chrysanthemum (Singh et al, 2015), bahkan sebagai peredam dan bahan konstruksi bangunan di lahan basah (Danley-Thomson et al, 2016).…”
Section: Pendahuluanunclassified